Triumphal Arch, Golden Gate International Exposition, San Francisco (H.S. Crocker Co., Inc.)
The graceful Arch of Triumph reflected in the fountains of the Court of Flowers at the Golden Gate International Exposition on Treasure Island in San Francisco Bay. Through the Arch a glimpse of the Siamese umbrella lanterns in the Court of Reflections.